Posthuman Enquiry in the Grip of the Binaries in Jeanette Winterson' s Frankissstein - Ayyildiz, Nilay Erdem (Alexandru Ioan Cuza Univ Iasi Fac Philosophy & Social-Political Sciences, 2023)
Jeanette Winterson's Frankissstein: A Love Story (2019) draws analogies to Mary Shelley's Frankenstein; or, the Modern Prometheus (1818), which is a protocyberpunk novel. The postmodern novel interweaves Mary Shelley's writing of Frankenstein in Switzerland and transgender Ry Shelley's acquaintance with artificial intelligence in Britain. Frankissstein also connects the tale of the Titan Prometheus, Professor Victor Frankenstein creating a cyborg in Frankenstein and Ry's beloved, Victor Stein, experimenting on cyborgs with artificial intelligence. Thus, the novel's narrative switches between the nineteenth and the twenty-first centuries to depict the posthuman condition over the centuries. What it means to be human, the validity of grand narratives and all kinds of binarism are put into question throughout Frankissstein as a postmodern extension of the nineteenth-century novel Frankenstein. The paper argues that the novel provides insights into the posthuman condition through technocultural discourses. A posthumanist reading of the novel indicates that Frankissstein contributes to the deconstruction of anthropocentric binaries in humanist thinking regarding the relationship between not only humans and nonhumans but also men and women. The study also reveals that despite the time lapse, the concerns related to the posthuman condition remain the same because transgressing dichotomies lead to ambiguity in human's life.
Keywords: posthuman; binaries; Jeanette Winterson; Frankissstein; Frankenstein